Carl Nielsen and Tivoli - Ketting, Knud (Carl Nielsen Studies, 2003)
The basis for the article is a complete overview covering every performance of music by Carl Nielsen in the summer season of the Copenhagen pleasure garden, Tivoli, during the composer’s lifetime (1865-1931). For the first years after becoming a professional violinist, Nielsen made his living from playing in the Tivoli orchestra. And it was in Tivoli he made his official debut as a composer in 1887. When his fellow student from the Academy of Music, Frederik Schnedler-Petersen at the beginning of the summer season 1909 took over as musical director in Tivoli, the Nielsen performances really took flight. The article lists in all 744 performances, which stylistically range right from the popular songs to the symphonies. Schnedler-Petersen was not afraid to present the rather conservative Tivoli audience with some musical challenges whenever the orchestra’s rather tight work-schedule permitted a moment for rehearsing these. But as Nielsen’s music became increasingly experimental, he too had to give up. The sixth symphony (1925) was only performed once in Tivoli and the clarinet concerto (1928) not at all. Nielsen’s birthday on the 9th June was in the Tivoli season and Schnedler-Petersen nearly always found some way of marking the event. Nielsen’s 60th birthday in 1925 was particularly festive with performances by the three Tivoli orchestras, a torchlight procession and a banquet in one of the best restaurants in Tivoli. Finally the article also briefly describes Schnedler-Petersen’s efforts outside Tivoli on behalf of Carl Nielsen, not least abroad where he was without any doubt the composer’s most diligent musical ambassador.